Heidegger and moral realism - Gupta, Anoop (Eugene, Oregon : Pickwick Publications, 2015)
"Is it possible to found a Heideggerian ethic around the notion of a relationship to being (Bezug zum Seyn)? Going against much of the Western tradition, Gupta considers if the being-relationship could result in a feeling or mystical experience that is the basis of ethics. Along the way, such an affective and embodied approach to ethics brings us into dialogue with a range of thinkers, such as Kant and Schweitzer. Further, it is suggested that an environmental philosophy is consistent with a Heideggerian ethics. Finally, recent research in the neurosciences is marshaled to at least show the plausibility of Heidegger's brand of moral realism as it is developed." --
HKBU library
YT2025 M08
Keywords: Heidegger, Martin, -- 1889-1976.; Moral realism